Clinical and Pathomorphology Diagnosis and Measures to Combat Cattle Leukemia in the Republic of Karakalpagistan - Aytbaeva M.B.; Murodov X.U. v.f.f.d; Isakov Aybek (American Journal of Biodiversity, 2025)
This article studied the prevalence of leukemia among cattle, as well as its etiological factors. To do this, the epizootic situation was checked for infectious diseases of cattle in 5 farms of the Republic of Karakalpakstan. Selected for examination on the recommendation of veterinary staff. A scientific and practical explanation of the incidence of leukemia in livestock farms, farms, clusters, LLC and private entrepreneurs of the Republic of Karakalpakstan was carried out